Television in the Formation of Civil Society: The Role of a Non- Controversial Public Space in Hong Kong - Lee, Paul S. N. (Television, Regulation and Civil Society in Asia, 2002)
Television first appeared in Hong Kong in 1957. It was a cable television service run by the Rediffusion Company which had operated a highly successful wired sound broadcasting service since 1949. Hong Kong was the first British colony to have television. But the Rediffusion television service was very expensive. Its monthly subscription fee was HK$55. In 1958, a technical worker’s monthly wages were HK$360 and an unskilled worker earned only HK$75 (Hong Kong Government 1959: 32). A year before the introduction of free-to-air television in 1967, Rediffusion television had only 67,000 subscribers (Hong Kong Government 1967: 206). Thus before 1967 television was an elite medium and its social impact was minimal.
Num Pages: 8
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Num Pages: 1
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Changing Contexts, New Texts: ‘‘Inserting’’ TV into the Transforming Text of Post-1980 Bengali Cinema - Gooptu, Sharmistha (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter analyses a profound transformation of Bengali regional-languagecinema since the early 1980s, a transformation that fundamentally changedthe industry and one that can arguably be attributed at least partly to thecreation of a Bengali television-watching public in the same period. Itfocuses on a trend that emerged in mainstream Bengali cinema during the1980s and was sustained thereafter, and brought into prominence a newconfiguration of elements previously marginal to Bengali films. This trans-formation was to do with mainstream Bengali cinema’s increasing adaptation of what are commonly known as the ‘‘masala’’ or ‘‘formula’’ elementsof Bombay cinema such as racy dialogues, stereotypical villainous char-acters, stylized fights and song-and-dance sequences. This new genre, whichhas commonly been discredited as the Bengali film industry’s totally unim-aginative imitation of the popular Hindi-language cinema of Bombay,completely altered what had been the dominant aesthetic of Bengali cinematill about the mid-1970s. Until this point, Bengali cinema was marked by itsclose relationship with Bengali literature and a Bengali middle-class worldview, greater realism than Bombay cinema or other mainstream regionalcinemas, and naturalistic acting styles, and was radically transformed by agrowing adoption of the ‘‘formula’’ elements commonly identified withpopular Hindi cinema. Industry sources, however, indicate that this newtrend was successful in boosting the Bengali film industry, which had beenswamped by a severe economic crisis since the 1970s. The industry’s crisiswas caused by a host of factors: the most important of these was the Ben-gali middle-class audience’s shift to television as a result of an increasingly unsatisfactory film-going experience in this period. The creation of a Ben-gali television public in the early 1980s shifted audiences from the cinematheatres, thereby significantly reducing film revenues in Calcutta, until then the prime market for Bengali films.
Num Pages: 11
Keywords: 1-Cinéma; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

‘Give Me a Vote, and I Will Give You a TV Set’: Television in Tamil Nadu Politics - Ranganathan, Maya (Television in India: Satellites, Politics and Cultural Change, 2008)
The role of television in democratic politics has been a subject of politicalcommunication studies at least since John F. Kennedy’s performance ontelevised debates supposedly turned around his electoral fortunes and wonhim the 1960 US presidential election. In India too, the potential of themedium in political communication has mostly been analysed in the contextof how television coverage of political leaders and parties, or the lack of it,affects voting behaviour. This chapter differs in its approach. In analysing television’s role in electoral politics in the southern Indian state of Tamil Nadu, it does not look at discourses prevalent on television. Instead, itunderscores how the medium itself has become a part of political discourse,particularly during elections. It points out how television acquired centre-stage as an electoral issue in the 2006 Tamil Nadu assembly elections, evengoing to the extent of dictating poll alliances. Tamil Nadu offers an inter-esting case study to understand the interface between television and Indianpolitics not only because Tamil films and state politics have been inex-tricably intertwined for decades, but also because the two notable political parties in the state have a stake in the private satellite television business.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Num Pages: 30
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

The Mahatma didn’t like the movies and why it matters: Indian broadcasting policy, 1920s–1990s - Jeffrey, Robin (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter examines the ideological and structural foundations of Indianbroadcasting policy as it developed from the 1930s to the 1990s. The chapter argues that the failure of Indian governments to make the most of radioand television for economic and social development stemmed from threesources: (i) the restrictive policies inherited from a colonial state, (ii) thepuritanism of the Gandhian national movement, and (iii) the fear, madevivid by the 1947 partition, of inflaming social conflict. The policies andinstitutions established in the 1940s and 1950s shaped Indian broadcasting for the next 40 years and have been significantly subverted only since 1992as a result of the transformation effected by satellite television.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Prime Time Soap Operas on Indian Television - Munshi, Shoma (Routledge India, 2020)
This book examines the phenomenon of prime time soap operas on Indian television. An anthropological insight into social issues and practices of contemporary India through the television, this volume analyzes the production of soaps within India’s cultural fabric. It deconstructs themes and issues surrounding the "everyday" and the "middle class" through the fiction of the "popular". In its second edition, this still remains the only book to examine prime time soap operas on Indian television. Without in any way changing the central arguments of the first edition, it adds an essential introductory chapter tracking the tectonic shifts in the Indian "mediascape" over the past decade – including how the explosion of regional language channels and an era of multiple screens have changed soap viewing forever. Meticulously researched and persuasively argued, the book traces how prime time soaps in India still grab the maximum eyeballs and remain the biggest earners for TV channels. The book will be of interest to students of anthropology and sociology, media and cultural studies, visual culture studies, gender and family studies, and also Asian studies in general. It is also an important resource for media producers, both in content production and television channels, as well as for the general reader.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Koweït (lieu de production du savoir); _Nettoyé

Culture, Politics, and Television in Hong Kong - Ma, Eric Kit-wai (Routledge, 1999)
Ma looks at the ways in which the identity of Hong Kong citizens has changed in the 1990s especially since the handover to China in 1997. This is the first analysis which focuses on the role, in this process, of popular media in general and television in particular. The author specifically analyses at the relationship between television ideologies and cultural identities and explores the role of television in the process of identity formation and maintenance.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Taiyu Serial Dramas in Taiwan: A History of Problem-Making - Irene Yang, Fang-Chih (Television Histories in Asia, 2015)
The construction of a problem, be it a crisis or a moral panic, is an attempt of policing and control, for the maintenance of hegemony and authority (Hall et al. 1978 ). A problem emerges as a problem only when it is out of its proper place, just like dirt becomes dirt only when it is not properly placed in the earth. The elimination of dirt is necessary in maintaining the cleanliness of the social order (Douglas 2002 ). In other words, it is the need for a particular social arrangement that constitutes the existence of a problem. Taiyu, the lingua franca of the Taiwanese, became a problem of dialect (called Minnanyu) to be eliminated when the KMT colonial regime moved to Taiwan, building it as a Chinese nation and instituting Mandarin as the national language. Television is central to the building of the Chinese nation. Taiyu serial dramas were broadcast soon after the fi rst network was established in 1962, but have been constructed as the most problematic and debased genre since the early 1970s when the second TV station, CTV (1969), and the third, CTS (1971), were established and used serial drama to compete for profi t. Accusations directed at the poverty of its quality and the vulgarity of the audiences have characterized mainstream criticisms and constructions of Taiyu serial dramas as problems from the 1970s to the present. This chapter investigates not only the how and what but also the why of this problem-construction, as an attempt to understand the power mechanisms at work in struggling for hegemonic control. It charts two historical moments – the 1970s and from the 1990s to the present – when language has played a signifi cant role in the articulations of serial dramas as problems and explores the changing political, economic and cultural forces that situate them as problems worthy of discussion. I argue that the history of this problem-making demonstrates the centrality of Chinese culture in political domination through cultural means, with ethnic/class politics playing a central role in the maintenance of a hierarchical social order. In the 1970s, Chinese culture was used to create ethnic/class divisions within Taiwan while simultaneously creating the illusion of a symbolic whole under the name of the Republic of China. However, since the 1990s, and intensifying after the 2000s, with the entanglement of democratization and neoliberalization in Taiwan and the rise of China, the ethnic/class tension is not just complicated by confl icted national identifi cations and Chinese culturepromoted by both the KMT Party’s Republic of China and the People’s Republic of China, but also for unifi cation purposes. While democratization, which involved the search for Taiwanese identity, led to the rise of Taiyu-based Hsiangtu drama, the neoliberal defi nition of culture as economic resource, which consecrates Chinese culture through capital investment, facilitates this unifi cation process while creating further ethnic/class/national identity divisions within Taiwan. The result is a disparaging of Taiyu-based culture in general and, in particular, Taiyu serial drama as a problem to be reformed.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

Tears, Talk, and Play: A Window to Gender and Sexuality on Tamil Television - Vangal, Uma (Channeling Cultures: Television Studies from India, 2014)
Tamil television lends itself to some interesting initiatives in gender empowerment through its programming in 3 categories – fiction, reality, and talent shows. This chapter provides a glimpse into television programmes on leading Tamil channels over the last decade (2000–10) from a gender perspective. Focusing particularly on women and transgender characters/hosts, emotional and psychological quotients of the shows and their audiences, moments of dramatic intensity, the chapter demonstrates how the vernacular televisual representations were quite different from the stereotypical portrayals of the mainstream ‘national’ television, even though the programmes were produced, televised, and received within the broader patriarchal framework of Tamil cultural and political contexts. The chapter, as a whole, intends to look at the production, representation and identification of Tamil television soaps and reality shows as vehicle for spotlighting gender issues and alternative sexualities in the public domain.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Sange ThakunBangla News Channels and Media-Citizenry - Gupta, Nilanjana (Channeling Cultures: Television Studies from India, 2014)
With special reference to the current scenario in West Bengal, this chapter argues that the rise and popularity of Bangla news channels like Star Ananda, 24 Ghanta, Kolkata TV, and Tara News have resulted in the emergence of a vernacular style of news broadcasting which is quite distinct from that of global or national news media. One major point in this chapter is how the vernacular news channels encourage particular forms of address — the emotional, the intimate and the melodramatic — and how close-ups and sound bites create particular kinds of telegenic political leaders who can use these formal characteristics to their advantage. This chapter explores the ways in which a distinctive kind of vernacular is reconfiguring the nature of political participation itself and hence the notion of citizenship and perhaps even the nature and functioning of the nation-state in India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

NDTV 24x7 Remix: Mohammad Afzal Guru Frame by Frame - Hutnyk, John (Channeling Cultures: Television Studies from India, 2014)
This chapter looks, in particular, at issues surrounding the trial of Mohammad Afzal Guru in 2006–7, but also with reference to the terrible Mumbai attacks of November 2008. Whilst tragic in multiple ways, these events are also made spectacular, emotive, and divisive, according to interpretation by television. The framing of television news in India could be several, but is often not. Pantomime terrors, extravagant formatting, phone-in trial reports seem to be the order of the day. The station ident, newsreader-presenter and video confession all contest for screen attention in the trial of Mohamed Afzal, and the ground for this was prepared long ago. This short history of a 24 hour news channel ends with ‘The Big Fight’ - a staged and theatrical mode of ‘infotainment’ that sacrifices intelligent reporting for ideological fit.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Inde (corpus analysé); Vietnam (lieu de production du savoir); _Nettoyé

When Live News was Too Dangerous: The Early History of Satellite TV in India - Mehta, Nalin (Channeling Cultures: Television Studies from India, 2014)
A unique confluence of technological, political and economic factors in the 1990s drove the transformative process that led to the battering down of the government’s monopoly over television. By the end of the 1990s, the growing strength of Indian capitalism after the liberalization of the Indian economy and the forces of what Thomas Friedman has called ‘Globalisation 3.0’ allowed Indian entrepreneurs to level the playing field. The Indian state, having embarked on economic liberalization, was forced to adapt to satellite television as an agent of global capitalism it certainly did not give up control over television easily or voluntarily. Operating at the junction of public culture, capitalism and globalization, satellite news networks have had profound implications for the state, politics, democracy and identity formation. Despite all their shortcomings and sensationalism, the emergence of satellite television news networks has enhanced and strengthened deliberative Indian democracy.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Television News and an Indian Infotainment Sphere - Thussu, Daya Kishan (Channeling Cultures: Television Studies from India, 2014)
The exponential growth of television news in India – from one state controlled network until 1991 to more than 100 news channels in 2012 – has transformed broadcast journalism in the country. This proliferation of news networks has intensified competition for audience and advertising revenue, leading to excessive marketization of news, which increasingly veers toward infotainment. The chapter examines the challenges faced by Indian television news – focusing on economic and political dimensions of television news - and its implications for the world’s largest democracy.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (lieu de production du savoir); Inde (corpus analysé); _Nettoyé

From Clients to Consumers: The Missing Citizens among the Indian Television Audience - Sinha, Dipankar (Channeling Cultures: Television Studies from India, 2014)
Beneath many instances of ’sweeping’ change, both structural and representational, in the market-dominant, liberalized and privatized Indian televisual scenario there lies a hidden transcript of continuity insofar as the encoding of development issues, images and messages is concerned. In the periods of Doordarshan and later corporate channels, though with markedly different historical contexts, reference points, contents and styles — the encoding of ’development’ leaves little autonomy to the audiences. In a political slant indicating how the two televisual periods converge in contracting the space for public debate and civic engagement the essay seeks to make a departure from the dominant view which puts them in binary positions.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

TV after Television Studies: Recasting Questions of Audiovisual Form - Roy, Abhijit (Channeling Cultures: Television Studies from India, 2014)
This chapter locates India, and broadly the post-colonial context, within the larger debates concerning television’s audiovisual form and mode of address. It tries to demonstrate that certain key traits in Indian popular performative traditions, representing an ‘alternative’ negotiation with modernity, are somewhat homologous with what western theorists have tried to specify (though in contradicting terms) as the features of televisual mode of address and ‘flow’. The chapter reads the specific imports of this correspondence in histories of Indian television with special reference to a somewhat novel way television has started imagining the nation after liberalization. The significance of the Indian popular film form as lending a major legacy to tele-viewership in India constitutes a major strand of argument.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Reformatting the Format: Philippines in the Global Television Format Business - Santos, Joseﬁna M. C. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In the eyes of many observers the Philippine cultural icon that is synonymous with travel, as well as being the subject of numerous advertisements is the jeepney, a public-transport vehicle assembled in the style of the US military jeep but lengthened to accommodate from fourteen to twenty-two sitting passengers. What distinguishes the jeepney from run-of-the-mill public transport however is its artistic décor: a clutter and kaleidoscope of various artefacts from miniature steel horses dotting the hood, to massive, jazzy plastic or steel billboards announcing the name of the jeepney, to murals painted in ﬁesta colours at the sides, to a bizarre combination of items in the front windshield juxtaposing conﬂicting images of the Sto. Nino (the baby Jesus Christ) and stickers with sexually risqué messages.
Num Pages: 12
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Closing the Creativity Gap – Renting Intellectual Capital in the Name of Local Content: Indonesia in the Global Television Format Business - Kitley, Philip (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
From time to time certain television shows ‘stop the nation’. In 2002 the localized version of the Celador licensed format2 Who Wants To Be A Millionaire? glued over a third of Indonesian television households to their screens at 7pm on Saturday nights.3 Is it the vicarious thrill of winning undreamed-of riches in a country which has been the slowest to recover from the Asian economic crisis of 1997 that attracts the audience? Circuses without bread? Perhaps, but this phenomenon is probably not profoundly related to local matters. We need look no further than the thin, phosphor coated screen. Millionaire, as it is referred to in television circles in Jakarta, is entertaining television. As other chapters testify, it has wowed viewers in countries in very varied economic circumstances. Millionaire is just one of a number of quiz and game show formats screening across all channels in Indonesia and is representative of the core business of international format providers in Indonesia which has been growing steadily since 1994.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Australie (lieu de production du savoir); Indonésie (corpus analysé); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Num Pages: 16
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Let the Contests Begin! ‘Singapore Slings’ into Action: Singapore in the Global Television Format Business - Lim, Tania (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Why is the hit Singapore edition of Who Wants To Be A Millionaire? must-see TV?1. Watch it so that you can hold the ‘hottest topic’ with your friends. 2. So you can be encouraged by the courage of some contestants who are bold enough to brave national TV when apparently they have not read enough. 3. So you can judge for yourself if you are bold (and knowledgeable) enough to brave national TV for your possible 1st million. 4. So you can call the number on screen and make your 1st million. 5. Finally, watch it to see for yourself that Singaporeans are not as well read and as globalized as we all think we are.
Num Pages: 17
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

Coping, Cloning and Copying: Hong Kong in the Global Television Format Business - Fung, Anthony (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Hong Kong is famous internationally as a ﬁnancial market, a shopping paradise, and Chinese ﬁlm production hub, but notoriously (and perhaps even attractively for some) Hong Kong is also a hotbed of piracy of computer software, DVDs, watches and toys.1 While many cultural products such as television dramas and movies are original and quite reputable in the region, media critics argue that the copycat phenomenon, which includes borrowing, inserting and modifying other cultural texts to augment local production, is common in the media and entertainment industries (Fung 1998). Whenever a new form, style, or popular culture trend emerges in Hong Kong, market forces soon kick in to replicate it. However, this kind of reproduction, as shown by the history of cultural production in Hong Kong, does not necessarily lead to a degradation of programme quality. Reproduction is not only a savvy strategy to reduce the ﬁnancial risks inherent to new products, but also aims at producing ‘improved’ versions which can reap more proﬁts for the industry.
Num Pages: 14
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé

Cloning, Adaptation, Import and Originality: Taiwan in the Global Television Format Business - Liu, Yu-Li; Chen, Yi-Hsiang (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Taiwan residents enjoy one of the most abundant television diets in East Asia. Eighty per cent of households subscribe to cable television services, offering a buffet of more than eighty channels including niche and full service channels. Taiwan’s television industry, while relatively small in comparison with its competitors in East Asia, has established a reputation for creatively re-generating formats developed elsewhere.
Num Pages: 20
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Taiwan (corpus analysé); Taiwan (lieu de production du savoir); _Nettoyé

A Local Mode of Programme Adaptation: South Korea in the Global Television Format Business - Lee, Dong-Hoo (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television has been called ‘a Western-originated project’ (Barker 1997: 5) and an institution of Western capitalist modernity. The global circulation of Western-centred, or more speciﬁcally, American-centred cultural products, contributes to the formation and dissemination of a global shared culture that reaches across the boundaries of nation-states. In the process American cultural products play a role in the formation of local television cultures.
Num Pages: 18
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Corée du Sud (corpus analysé); Corée du Sud (lieu de production du savoir); _Nettoyé

Feeling Glocal: Japan in the Global Television Format Business - Iwabuchi, Koichi (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
In March 2001 a Japanese newspaper report entitled ‘Indians are addicted to a quiz show’ drew attention to a phenomenally popular television programme in India – a quiz show that attracts millions of viewers in which challengers strive to win prize money (Asahi Shinbun 2001). What was particularly eye-catching for the journalist was the proﬂigately decorated studio set located in Mumbai (Bombay) and the caring guidance of the MC, a ﬁlm star famous in India. The name of the show, as you might have already inferred, was Who Wants To Be A Millionaire?.
Num Pages: 15
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Japon (corpus analysé); Japon (lieu de production du savoir); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Transnational Latin American Television: Genres, Formats and Adaptations - Ribke, Nahuel (Routledge, 2020)
This book examines the process of transnationalization of Latin American television industries. Drawing upon six representative case studies spanning the subcontinent’s vast and diverse geo-political and cultural landscape, the book offers a unique exploration of the ongoing formation of interrelated cultural, technological, and political landscapes, from the mid-1980s to the present. The chapters analyse the international circulation of the genres and formats of entertainment television across the subcontinent to explore the main driving forces propelling the production and consumption of television contents in the region, and what we can learn about the cultural and social identities of Latin American audiences following the journey of genres, formats, and media personalities beyond their own national borders. Taking a contemporary interdisciplinary approach to the study of transnational television industries, this book will be of significant interest to scholars and students of television and film studies, communication studies, Latin American studies, global media studies, and media and cultural industries.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Asie (lieu de production du savoir); Israël (lieu de production du savoir); _Nettoyé

The Little Emperors’ New Toys: A Critical Inquiry into Children and Television in China - Zhao, Bin (Springer, 2013)
Drawing on original research I conducted in the late 1980s, the book argues for a critical approach to the study of children and television. It begins with critical reappraisals of previous empiricist and interpretative studies to set the ground for a different theoretical inquiry which links biography with history. The situated activity of children's television viewing therefore has to be related to the broader historical and cultural formations in post-Mao China. By way of a methodological pluralism of questionnaire survey, in-depth interviews and observation, the book provides the reader with a thorough critical analysis of the rise of the new commercial ethic in Chinese society in general, and in the sector of media and communications in particular, at the very historical turning point of the late 1980s. Soon after that, Deng Xiaoping made his significant tour to south China, reckoning a big step forward towards further liberalization and started to form a brave new world in China ever since.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Chinese Television and Soft Power Communication in Australia - Li, Mei (Anthem Press, 2019)
Chinese Television and Soft Power Communication in Australia discusses China’s soft power communication approach and investigates information handling between China and its targeted audiences in the eyes of key influencers – intermediate elites (public diplomacy policy elites in particular) in China and Australia. It explores CGTN (with staff from several professional cultures) and conducts a systemic test of how successful/unsuccessful China’s soft power message projection is in terms of congruence between projected and received frames as a pivotal factor of its power status. The analysis is based on a case study of frames in the messaging on Chinese international TV about China’s Belt and Road Initiative and in the minds of Australian public diplomacy policy elites. The question raised is whether and how Australia is listening.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Australie (corpus analysé); Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Television in Bangladesh: News and Audiences - Roy, Ratan Kumar (Routledge India, 2020)
This book examines the role of 24/7 television news channels in Bangladesh. By using a multi-sited ethnography of television news media, it showcases the socio-political undercurrents of media practices and the everydayness of TV news in Bangladesh. It discusses a wide gamut of issues such as news making; localised public sphere; audience reaction and viewing culture; impact of rumours and fake news; socio-political conditions; protest mobilization; newsroom politics and perspectives from the ground. An important intervention in the subject, this book will be useful to scholars and researchers of media studies, journalism and mass communication, anthropology, cultural studies, political sociology, political science, sociology, South Asian studies, as well as television professionals, journalists, civil society activists, and those interested in the study of Bangladesh.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Bangladesh (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Film and Television Culture in China - Zhifeng, Hu (Paths International, Limited, 2018)
Film and Television Culture in China gives a provocative analysis of film and television culture in China. The author first gives a panoramic picture of Chinese culture in which film and television was born and shaped. He then delineates the definition, composition, and basic relations in film and television culture. Also discussed are the two traditions in Chinese film and television culture–the worldly spirit and the poetic style. The two traditions are deeply rooted in Chinese Confucianism and Taoism, and have influenced Chinese film and television from the start. The author provides in-depth and original readings of the phenomena in Chinese film and television culture, such as: the reform films and the reflection films; the character and mission of television documentary; and a dialogue between the mainland and Taiwan. Film and Television Culture in China will be an essential guide to understand the film and television culture in China, from early screen to the present day.
Keywords: 1-Cinéma; 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Arab Television Industries - Khalil, Joe; Kraidy, Marwan M. (BFI Publishing, 2009)
In recent years, Arab television has undergone a dramatic and profound transformation from terrestrial, government-owned, national channels to satellite, privately owned, transnational networks. The latter is the Arab television that matters today, economically, socially and politically. The resulting pan-Arab industry is vibrant, diverse, and fluid - very different, the authors of this major new study argue, from the prevailing view in the West, which focuses only on the al-Jazeera network. Based on a wealth of primary Arabic language sources, interviews with Arab television executives, and the authors' personal and professional experience with the industry, Arab Television Industries tells the story of that transformation, featuring compelling portraits of major players and institutions, and captures dominant trends in the industry. Readers learn how the transformation of Arab television came to be, the different kinds of channels, how programs are made and promoted, and how they are regulated. Throughout, the analysis focuses on the interaction of the television industry with Arab politics, business, societies and cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; Qatar (lieu de production du savoir); _Nettoyé

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Cinema and Television in Singapore: Resistance in One Dimension - Tan, Kenneth (BRILL, 2008)
Through close readings of contemporary made-in-Singapore films (by Jack Neo, Eric Khoo, and Royston Tan) and television programs (Singapore Idol, sitcoms, and dramas), this book analyzes the prospects of resistance in an advanced capitalist-industrial society with "global city" aspirations.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

New Television, Globalisation, and the East Asian Cultural Imagination - Keane, Michael; Fung, Anthony Y. H.; Moran, Albert (Hong Kong University Press, 2007)
This volume is divided into three parts: 'Adaptation and Local Production in East Asia', 'Formats, Clones, and Generic Variations' and 'New Television'.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Chine (corpus analysé); Corée du Sud (corpus analysé); Hong Kong (corpus analysé); Hong Kong (lieu de production du savoir); Japon (corpus analysé); Taiwan (corpus analysé); _Nettoyé

Consuming Halal Turkish Television in Indonesia: A Closer Look at the Social Responses Towards Muhteşem Yüzyıl - Rakhmani, Inaya; Zakiah, Adinda (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter unpacks the tension between secular, modern values and conservative, Islamic interpretations within the Indonesian middle class by taking the consumption of Turkish popular cultural products as a case. The chapter explicates the social responses towards the first Turkish television drama aired on terrestrial, private television in Indonesia: The Magnificent Century (Muhtesṃem Yüzyıl/Abad Kejayaan). This chapter understands the reproduction of secular and conservative Islamic values, while in contestation, as a response to broader global, market-capitalist developments. It finds that in response to audience criticism regarding the “un-Islamic” portrayal of the epoch in the drama—specifically the depiction of women as concubines—television stations enlisted the services of Muslim clerics to correct or justify the representation of historical facts. This reveals that market-driven self-censorship has opened up ways for Muslim clerics to influence television content. As such, the chapter argues that market-capitalist forces discursively use Islamic authority as a way to legitimise the halal consumption of Turkish drama among Indonesian Muslim audience at the expense of programme diversity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Indonésie (corpus analysé); Indonésie (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Continuities and Changes in the Transnational Broadcasts of TRT - Karanfil, Gökçen (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter traces the evolution of the Turkish Public Service Broadcaster with a focus on its transnationalization. Drawing parallels between the changing dynamics in politics, culture, and media in Turkey; contemporary cosmopolitan media cultures; and the continuities and changes in Turkish Radio and Television Corporation’s (henceforth TRT) identity as a public service broadcaster, I shed light on the ways in which TRT has been engaging in transnational broadcasts since the beginning of 1990s. For this I elaborate on the ways in which transnational broadcasting processes in Turkey have been influenced by media transnationalization around the world. I discuss two different incentives behind TRT’s transnational endeavors. First, I elaborate on TRT’s attempts at engaging with the Turkish diaspora around the world; later, I articulate how, in more recent years, TRT sets out to exert a Turkish cultural presence in the Middle East and North Africa (MENA) region. The chapter aims to draw a general portrait of the concept of transnational broadcasting in Turkey with a specific focus on the country’s public service broadcaster, TRT.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

TV China: Control and Expansion - Zhu, Ying (The Routledge Companion to Global Television, 2019)
The chapter traces the evolution of Chinese television since 1958 from a state propaganda organ to a profit-generating media juggernaut, with China Central Television (CCTV) as the only network TV responding to both market principles and party directives. Commercialization and marketization played a major role in the rapid development of the Chinese television industry. In recent years China’s TV industry has witnessed the rise of private media companies and the rapid expansion of digital media and the proliferation of over the top (OTT) content. The chapter further provides an overview of China’s overall TV structures and teases out the relationship between CCTV and local stations. The most popular genre on Chinese TV is serial drama, which developed from predominantly single-episode anthology dramas in the 1980s to chiefly multi-episode serial dramas. Talk shows and reality TV became fashionable since the late 1990s.
Num Pages: 9
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Chine (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé; États-Unis (lieu de production du savoir)

Arab Television Industries: Enduring Players and Emerging Alternatives - Khalil, Joe F. (The Routledge Companion to Global Television, 2019)
This chapter provides an overview and analysis of emerging alternatives in the context of Arab television production, programming, and distribution. Media convergence and the access to digital technologies have accentuated the fragmentation of audiences, revenue streams, and forced alliances and competitions between previously discrete sectors of the media business. Yet, alternative practices are closely associated with changing political, economic, and cultural vectors in the Arab region and the increasing integration of its television industries in global media. The chapter argues that these alternatives constitute a set of continuities with the history of Arab television. Taken together, they also demonstrate some level of transformation in production practices, programming strategies, and distribution operations.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Qatar (lieu de production du savoir); _Nettoyé

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Amateur Gold Farming in China: “Chinese Ingenuity,” Independence, and Critique - Liboriussen, Bjarke (Games and Culture, 2016)
Informed by a mix of theoretical sources and interviews with middle-class Chinese amateur gold farmers, this article argues that within China, the figure of the Chinese gold farmer might function as focus for reflection on Chineseness and China’s role in an increasingly interconnected world, rather than as a carrier of third-world stereotype as it tends to do in the West. The concept of shanzhai—often associated with sometimes comical, sometimes innovative Chinese copying of foreign consumer goods—is employed as a key analytical tool and helps highlight the themes of “Chinese ingenuity,” independence (from game operators and to some extent also parents), and critique (of games).
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

Sinological-orientalism in Western News Media: Caricatures of Games Culture and Business - Wirman, Hanna (Games and Culture, 2016)
From gold farmers and ‘100 million brain-damaged online gamers’ to the world’s biggest game company and more players than US citizens, China seems like the cabinet of curiosities for the whole world of digital gaming. This article focuses on news coverage around Chinese gaming and presents three phases of such journalism. China’s emerging games market was most prominently featured between 1999 and 2005, while 2006-2011 focused on extreme play behavior in China. Most recently, a discourse of vast business opportunities and stabilizing markets has been presented by Western news media. In total more than 853 news articles are explored in parallel to the theoretical concept of Sinological-orientalism. This article suggests significant historical changes in the ways in which knowledge of Chinese gaming has been produced in English language news media.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; _Nettoyé

A Critical Cultural History of Online Games in China, 1995–2015 - Chew, Matthew M. (Games and Culture, 2016)
This study critically assesses the Chinese online games industry through problematizing the creativity of Chinese games. I find that between 1995 and 2001, Chinese online games were mostly developed by amateurs, noncommercial, and considerably creative. Between 2002 and 2005, industrial growth allowed some room for local creativity despite commercialization and dominance of imported games. Current scholarly, business, and media discourses unfairly ignore creativity in these first two periods and yet praise the Chinese game industry’s commercial success since the late 2000s. I challenge these discourses by illustrating that between 2006 and early 2009, a new, ethically dubious, and uniquely Chinese business model emerged, became domestically dominant, and quietly and profoundly impacted on global online game design. From mid-2009 to 2015, there is ongoing corporatization based on the dubious Chinese business model on the one hand, and a reemphasis on creativity motivated by browser and mobile game formats on the other.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games With a Continuum: Globalization, Regionalization, and the Nation-State in the Development of China’s Online Game Industry - Jiang, Qiaolei; Fung, Anthony Y.H. (Games and Culture, 2019)
As a case study, this article examines the development of China’s online game industry and how China responds to the forces of globalization. Based on in-depth interviews, ethnographic research, and the analysis of archive documents from the past few years, this study identifies China’s evolving strategy of neo-techno-nationalism. In the Chinese context, this national strategy manipulates technology to create a version of popular nationalism that is both acceptable to and easily censored by the authorities. Therefore, cultural industries that adopt this strategy stand a good chance of prevailing in the Chinese market. This success explains why the regional competitors of Chinese online games—Korean games—are more successful in China than most of their Western counterparts. By providing a snapshot of the current ecology of China’s online game industry, this article also discusses the influence of regional and global forces in a concrete context and argues that the development of China’s online game industry depends more on political factors than economic factors.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"–Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Interview with Mira Wardhaningsih from StoryTale Studios on the Indonesian Horror Game Pamali - Trattner, Kathrin; Wardhaningsih, Mira (Gamevironments, 2019)
An interview by Kathrin Trattner with Mira Wardhaningsih, Cultural Content Director from StoryTale Studios about the game Pamali
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Round Table Discussion on Nation(alism), Identity and Video Gaming with Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee - Trattner, Kathrin; Condis, Megan; Didzgalvyt, Marijam; Hobmeier, Georg; Mukherjee, Souvik; Kienzl, Lisa (Gamevironments, 2019)
Questions of nation and identity not only concern multiple aspects of video games, their production, and their consumption, but also require further and manifold discussion from different perspectives. In an effort to bring together voices from different fields that engage with video games and gaming practices from various perspectives, this virtual round table discussion attempts to open up the conversation beyond the realms of academia. Kathrin Trattner and Lisa Kienzl talked to Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee about how concepts such as nation(alism) and identity impact video game representations, the gaming industry, and online gaming cultures in numerous ways.
Accepted: 2020-03-25T23:30:29Z
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Interview With Ryan Sumo, Lead Artist/Business Developer At Squeaky Wheel Studio - Radde-Antweiler, Kerstin; Sumo, Ryan (Gamevironments, 2018)
Interview with Ryan Sumo, Lead Artist/Business Developer at Squeaky Wheel Studio
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With Ben Joseph P. Banta, Founder Of Ranida Games - Radde-Antweiler, Kerstin; Banta, Ben Joseph P. (Gamevironments, 2018)
Interview With Ben Joseph P. Banta, Founder Of Ranida Games
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With The Creator Of Boo! Dead Ka! Game - Radde-Antweiler, Kerstin; Prieto, Kurt (Gamevironments, 2018)
Interview with With Kurt Prieto, Games Designer Of Boo! Dead Ka! Game
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio - Zeiler, Xenia; Zainuddeen, Fahadh (Gamevironments, 2018)
Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio, Hyderabad, India
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio - Zeiler, Xenia; Kumar, Avinash (Gamevironments, 2018)
Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games - Zeiler, Xenia; Singh, Avichal (Gamevironments, 2018)
Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games, Pune, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Satyajit Chakraborty, Founder of Flying Robot Studios, Kolkata, India - Zeiler, Xenia; Chakraborty, Satyajit (Gamevironments, 2018)
Accepted: 2020-03-25T23:30:08Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Video Game Development in Asia : a Research Project on Cultural Heritage and National Identity - Grieve, Gregory P.; Helland, Christopher; Radde-Antweiler, Kerstin; Zeiler, Xenia (Gamevironments, 2017)
A report of the 2017 collaborative research project Video Game Development in Asia. Cultural Heritage and National Identity.
Accepted: 2020-03-25T23:29:51Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Interview with Shailesh Prabhu, Indian Game Designer - Prabhu, Shailesh (Game Studies, 2016)
Interview with the Indian Game Designer Shailesh Prabhu about his game Sky Sutra.
Accepted: 2020-03-25T23:29:20Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Games Studies India Adda #6: Zahra Rizvi - Game Studies India Adda (Game Studies India Adda, 2021)
Playing Dystopia: Searching for the Neganthropocene in Papers, Please and Orwell The way we play games and the way games play us is constantly changing. The physical shrinking of space can no longer be compensated by expansive gamescapes which otherwise provided a reprieve from diminishing access to space in 20th and 21st century childhood (Mayra, An Introduction to Game Studies). Gamescapes, increasingly, are becoming neo-explorations of “other people simulators” characterized by a suffocating hypernearing of the experience of the dystopia (Lucas Pope). Often ‘mundane’ mirrors of real-life situations, these dystopian games place the player in movement-limiting, choice-limiting challenging scenarios from where a fulfilling ending is more often than not impossible. I look at two of these dystopian games that offer covertly disruptive gameplay through alienating, often disembodied, simulation as a strategy for playing dystopia: Lucas Pope’s Papers, Please and Osmotic Studios’ Orwell. Closely engaging with issues of surveillance, digital governance, neurotechnology, illegal profiling, and ultimately, survival in a dystopia of technics, these games with their multiple endings caused by the smallest, seemingly most insignificant of differences in gameplay become crucial in their playing out of the possibilities of the neganthropocene.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #4: Poonam Chowdhury - Game Studies India Adda (Game Studies India Adda, 2021)
Thatgamecompany’s 'Journey' (2012) is a videogame like no other. This serene atmospheric game came out at a time when fast-paced, aggressive, AAA games were (and still are) the norm. Soon after the game’s release in 2012, thatgamecompany’s courage and hard work started getting the appreciation it deserved. 'Journey' has won several ‘Game of the Year’ awards and received several other awards and nominations, including a ‘Best Score Soundtrack for Visual Media’ nomination for the 2013 Grammy Awards. For this Game Studies India Adda Talk, I will be discussing (read: gushing over) this game’s brilliant visual and auditory art, wordless storytelling techniques, and one-of-a-kind multiplayer experience. Please join me on this talk and let's take a ‘journey’ like no other. Pun intended. Thank you and I hope you all have a wonderful new year. 🙂 Here’s the game trailer: https://www.youtube.com/watch?v=Ie4iz...
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Games Studies India Adda Talk #3 The vanishing Curator - Game Studies India Adda (Game Studies India Adda, 2020)
Playing back to the Empire, in videogames, is rife with tensions. The imperialist sentiment inherent in reverse-colonist discourse featured in most strategy-based videogames like Europa Universalis IV, where the player could conquer Europe playing for the Marathas, has been noted by Souvik Mukherjee (2017) as playing into the colonial logic while futilely trying to challenge it. Studio Oleomingus, an Indian two-man game studio, is one of the few involved in a different experiment. Their mythical game Somewhere, chronicling a postmodernist search for identity and narrative in the forgotten city of Kayamgadh, has generated significant spin-offs into its universe. With attention to one such spin-off, I will focus critical attention on the issue of the postcolonial gaming of the Museum in A Museum of Dubious Splendors. I will examine the New Museological implications of A Museum of Dubious Splendors, keeping in mind Museologist Eilean Hooper-Greenhill’s assertion of museums embodying “the power to name, to represent common sense, to create official versions, to represent the social world, to represent the past” (Hooper-Greenhill 2001: 2). Oleomingus’ own description of A Museum, as an adaptation of edited, mangled, contested short stories by a fictional Urdu writer, Mir Umar Hassan, eschews the linear narrative production of the colonial museum for a game of meanings, where the player enters rooms according to his choice and constructs his/her own “quiet game about prosaic objects and spurious histories.” ("A Museum" 2018) The paper would take this into account and examine the reconceptualization of the museum space with respect to James Clifford’s sense of museums being “contact zones”: A Museum’s lack of any curator, with its curious blend of colonial and native tales and banal objects defamiliarised by “spurious histories” lends itself to questions of playing the Empire back according to a different episteme, through subaltern histories that the colonial museum space silenced. Paying close attention to the question of postcolonial spatiality in this game, I will analyze the historiographical implications of these identity-scatterings and recuperations at constant play in the structure of the game. Keywords: Museum Studies, Thing Theory, Game studies, Marginal identity, Postcolonial Studies
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

GSI Adda Talk #2 Riko Banerjee What is it like to be a Gamer or pursue Game Studies in India? - Game Studies India Adda (Game Studies India Adda, 2020)
Video gaming is one of the most popular hobbies in the world, with the gaming industry grossing more revenue than the movie and the music industry combined. The estimated number of gamers across the whole world as of August 2020 is 2.7 billion, which is more than one-third of the world population. The benefits of gaming, as cited by numerous researchers, include a boost in confidence, improved cognitive abilities, stress relief, improved problem-solving skills, enhanced social skills among dyslexic kids, and among many others. Even though video gaming as a hobby and career is slowly getting recognition in India, majority of the population still scoff at the activity, shunning gamers and game researchers alike, citing out-of-context and sometimes even false media propaganda. The challenges faced by a typical gamer in India include lack of information, budget limitation, lack of support from parents and teachers when it comes to teenage gamers, and the overall lack of gaming as a mainstream culture among countrymen. As for someone who wants to pursue Game Studies, there is currently little to no provision for that due to the tightly knit education system in the country and the utter lack of educational institutes offering courses on game studies. We go on to further discuss all of the above challenges and experiences faced by a gamer or someone who wants to pursue game studies in India, in our detailed talk that is scheduled on November 21, 2020.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

First-Person Encounters #3: Prof. Xenia Zeiler - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we interview Xenia Zeiler, an associate professor of South Asian studies at the University of Helsinki, Finland. Her research is situated at the intersection of digital media, religion, and culture, with a focus on India and the worldwide Indian community.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Japanese Video Games and Comics in Singapore: Issues in Popularization, Localization and their Implications - Ng Wai-ming, Benjamin (N.D., 1999)
OCLC: 882102421
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Politics of Production: Videogames 10 years after Games of Empire - Hammar, Emil L.; de Wildt, Lars; Mukherjee, Souvik; Pelletier, Caroline (Games and Culture, 2021)
2019 marked ten years since the publication of Nick Dyer-Witheford and Greig de Peuter’s Games of Empire, which has become a seminal book in videogame cultural criticism. Ten years later, there is still a pressing need for cultural and materialist criticism of the politics of production within game studies. In putting together this special issue, our hope is to identify new developments in the game industry and academia that are emblematic of 21st-century capitalism. Just as Games of Empire popularised critical political-economic perspectives ten years ago, we encourage others, as the authors in this issue did, to continue and maintain investigations into questions of ownership, privatized property, coercive class relations, military operations and radical struggle. Such analyses are necessary not only to trace but also to open up new directions in game culture and academia for decades to come.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

The Lure of Pokémon: Video Games and the Savage Mind - Nakazawa, Shin'ichi (Japan Publishing Industry Foundation for Culture, 2019)
From its humble beginnings as a video game launched in the mid-90s, Pokémon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokémon GO. In the work, Nakazawa Shinichi argues that the Pokémon worldview is the best contemporary example of Claude Lévi-Strauss's "savage mind" (la pensée sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature.
Section: 1 v. (129 p.) : illustrations, couv. illustrations en coul. ; 22 cm
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Interpretation of a New “Creative Industry” in Turkey: Game Studios and the Production of a Value Chain - Binark, Mutlu; Bayraktutan, Günseli (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
In this chapter, the creation of a value chain during the process of digital games development in Turkey is discussed using a critical political economy approach. This study claims to be the first of its kind that intends to examine the topography of the digital game industry in Turkey and gives a brief history and describes the present status of digital games production in Turkey. All the components of a value chain, namely, the industrial structure and development process, publishing and licensing, distribution and marketing structure, labor force, legal regulations, and governmental policies will be considered in that order to map out the present topography of the industry. The final part of the study will deal with possible solutions for further development in the industry. At this point, the study stresses the fact that all components of the value chain must be performed uninterrupted if the actors in Turkey’s digital game industry desire to position themselves as “producers” in global or local markets.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Beautiful Fighting Girl - Saitō, Tamaki; Azuma, Hiroki (University of Minnesota Press, 2011)
From Nausicaa to Sailor Moon, understanding girl heroines of manga and anime within otaku culture.
OCLC: 897044808
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Creative Industries Across Cultural Borders: The Case of Video Games in Asia - Tschang, Ted (Creative Economies, Creative Cities: Asian-European Perspectives, 2009)
This chapter examines the relationship between culture, economics and policy within the creative industries (which for the purposes of this paper, are assumed to be equivalent to the cultural industries), and their manifestation in Asia. Addressing any one of these three issues is a challenge in itself, but addressing all three of them together raises the complexity even further. Early writers on the “creative economy” have noted how it works differently from the traditional economy (Florida 2002; Howkins 2001).1 Culture is vitally important to understanding how creative industries develop, but the role of culture in shaping national competitive advantage is not that clear. The same can be said for policy, and a discussion of the triad can be quite convoluted. Having said that, all three levels are still very relevant to the proper description of a creative industry — as I will show in this chapter.This paper attempts to address this triad of issues primarily with a production-and-innovation-oriented view of industrial organisation, bringing in creativity, culture and policy where possible. I shall do this primarily through the lens of one sector in particular — the video games industry — in which Asia has been investing heavily lately, and in which Japan has been an early leader. I will also provide a limited focus on the animation sector for comparative purposes. I will first provide a summary of how creative production in video games occurs in the US, followed by an examination of how Asian patterns compare. In particular, I am interested in whether individual and industrial level creativity differs in Asia. Within Asia, more detailed cases of the Chinese online games industry and the Philippine animation industry will be discussed, but relevant observations are also drawn from general knowledge and a literature review of Japan, Korea and Singapore, as well as interviews which corroborate those observations.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games in Asia - Ng Wai-ming, Benjamin (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Video Game Developpement Process - Tschang, Feichin Ted (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Japanese Video Games in Singapore: History, Culture and Industry - Ng Wai-ming, Benjamin (Asian Journal of Social Science, 2001)
Globalization of Japanese popular culture is reshaping the global cultural landscape. Some forms of Japanese popular culture (such as video games animation and sushi) are well-received internationally, whereas others (such as pop music, films and TV dramas) are only popular in Asia. Of all forms of Japanese popular culture, video game is perhaps the most powerful due to its strong universal appeal. It has dominated the world market since the mid-1980s. This article uses Singapore as a case study to demonstrate the global popularization of Japanese video games. There has been a boom of Japanese popular culture in Singapore in the 1990s. In particular, Japanese video games, comics and animation have become an integral part of youth culture in Singapore (Ng, March 2000: 234-246; Ng, May 2000: 44-56; Ng, June 2000: 1-14). Video game is a neglected topic in cultural studies. Although there are some basic studies of Japanese video games in the Western world (Hayes & Disney, 1995; Herz, 1997; Kinder 1991; Monopolies, 1995; Sheff, 1993), its impact in Asia is largely unknown. This article is a preliminary study of the Japanese video game culture and industry in Singapore from historical and socio-cultural perspectives, focusing on consoles, games and players. Based on interviews, questionnaires and data from newspapers and magazines, this research aims at pro viding a general overview of the history and impact of Japanese video games in Singapore. All the data and analyses are basic and this is beyond the scope of this paper to discuss any particular issue or theory in details. This paper consists of four sections. The first three sections outline the development of home video game consoles, handheld electronic games and game arcades respectively. The concluding section pinpoints the characteristics of the video
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

New Queer Sinophone Cinema: Local Histories, Transnational Connections - Pecic, Zoran 1981- (Palgrave Macmillan, 2016)
This book looks closely at some of the most significant films within the field of queer Sinophone cinema. Examining queerness in films produced in the PRC, Taiwan and Hong Kong, the book merges the Sinophone with the queer, theorising both concepts as local and global, homebound as well as diasporic.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé